Gender Equality in the Spotlight of Hadith Analysis of the Hadith's Views on the Values of Gender Equality Discourse - Ihsan Jamaluddin Junus; Nuril Khairani Niswatil Ula; Dadah Dadah; Badri Khaeruman; Aceng Abdulkodir (al-Afkar, Journal For Islamic Studies, 2026)
The issue of gender equality continues to be a topic of concern in religious discourse, particularly in contemporary Islamic studies. Some consider Islamic teachings to be patriarchal and biased against women. This raises critical questions about how hadith are understood and interpreted in the context of gender equality. This study aims to examine the hadith perspective on the issue of gender equality through a qualitative approach based on literature review. Data were collected from major hadith books, classical and contemporary exegetical literature, and related academic research. The analysis was conducted in three stages: content analysis to explore the meaning of hadith, comparative analysis of gender ideology, and interpretive analysis of hadith that contradict the values of gender equality discourse. The results show that many ideas on the issue of gender equality contradict the hadith of the Prophet Muhammad.